Case Report: Laparoscopic management of penetrating liver injury from pneumatic nail gun - Zhang, Mingyu; Li, Xuchi; Feng, Qingbo (Frontiers in Surgery, 2025)
Foreign bodies in the liver are relatively rare, with most cases resulting from ingested objects that migrate through the gastrointestinal tract. Direct hepatic penetration by pneumatic tools represents an exceptionally rare mechanism of injury, as these foreign bodies typically require significant force to breach the abdominal wall and lodge within the liver parenchyma. Preoperative differentiation between migrated and directly penetrating foreign bodies is clinically significant, as it may influence both diagnostic approach and surgical planning. Here, we report the diagnosis and management of a 50-year-old male with an unusual case of pneumatic nail penetration into the left hepatic lobe. The patient presented with acute abdominal pain following accidental penetration by a 5.2 cm pneumatic nail that traversed the rectus abdominis to lodge in segment III of the liver. CT imaging confirmed the nail's trajectory while demonstrating no evidence of abscess formation or pneumoperitoneum. Vital signs and laboratory parameters remained stable throughout the clinical course. During exploratory laparoscopy, the foreign body was identified within the left hepatic lobe, confirming its direct penetration pathway rather than migratory origin. The nail was successfully extracted using careful laparoscopic dissection, with complete preservation of surrounding parenchyma and no significant bleeding. The patient experienced an uneventful recovery and was discharged on postoperative day 2 with complete resolution of symptoms.